Jellyfish (Chrysaora lactea, Cnidaria, Semaeostomeae) aggregations in southern Brazil and consequences of stings in humans - Marques, Antonio C.; Haddad, Vidal [UNESP]; Rodrigo, Lenora; Marques-da-Silva, Emanuel; Morandini, Andre C. (Univ Catolica De Valparaiso, 2014)
The frequency of jellyfish blooms is generating a world-wide discussion about medusae population explosions, mainly those associated with stings. We report over 20,000 envenomations caused by Chrysaora lactea (Scyphozoa) in the State of Paranaa (southern Brazil) during the austral summer of 2011-2012. Envenomations were considered mild, but almost 600 cases were treated in emergency services, with either toxic and allergic reactions, some with systemic manifestations. We proposed non-exclusive hypotheses to explain this large number of cases.
Keywords: Chrysaora lactea; Scyphozoa; Jellyfish; Envenomation; Public health; Stings; Parana; Brazil